Global development finance : (World Bank, 2002)
This volume focuses on the effectiveness of international resource transfers. Topics covered include: recent trends and prospects for private capital flows; effectiveness of private capital flows in boosting investment and productivity; analysing progress in increasing the effectiveness of aid and the HIPC initiative; and financing international public goods.